Fresh Milk Technology. Milk Separation - Vereshchak, Dmitry (My University, 2014)
The fat fraction separates from the skim milk when milk is allowed to stand for 30 to 40 minutes. This is known a `creaming'. The creaming process can be used to remove fat from milk in a more concentrated form.
Keywords: технологія; молоко; сепарація молока; технология; сепарация молока; Fresh Milk; milk technology; separation; кафедра іноземних мов професійного спрямування